A Comparative Clinical Study Of Tail Dhara And Takra Dhara In The Management of Anidra w.s.r To Insomnia - Radder, Jagdish; Hadimani, G S; Sir, G Vinay Mohan (International Research Journal of Ayurveda & Yoga, 2021)
Background:-The impact of insomnia is far reaching and may affect both physical and emotional health as well as intellectual capacity. Understanding the potential causes of sleep disruption and the range of possible solutions will allow many to overcome the difficulty of disrupted sleep. The present study was undertaken to evaluate the efficacy of Tail Dhara with Karpasasthyadi Tail and Takra Dhara with medicated Takra (Butter milk) in Anidra (Insomnia) before and after treatment in Group A and Group B. Material and Methods:A sample size of 20, diagnosed cases of Anidra (Insomnia) were selected from the O.P.D &I.P.D of Shree Shivayogeeshwara Rural Ayurvedic Medical college & hospital Inchal, camps and other referrals. Results: Results obtained after the clinical trial was analyzed statistically and all the observations were subjected to creative discussions. Groups B showed significant result when statistically compared before and after the treatment with Group A, and when comparison between the two groups were done to know which, one is better compared to the other, it was shown statistically and clinically significant. Conclusion: Both the procedures were studied statistically, the results obtained by statistically both the groups have equal effect on Insomnia but clinically Taila Dhara is having slightly better result than Takra dhara.